The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1161/circulationaha.105.601005
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of Diastolic Function and Filling Pressure in Patients With Acute Myocardial Infarction

Abstract: A cute myocardial infarction (AMI) is characterized by regional myocardial damage that may lead to systolic and diastolic dysfunction with a subsequent risk of left ventricular (LV) remodeling, local and systemic neurohormonal activation, and vascular dysfunction. The pathophysiology and prognosis of LV systolic dysfunction after AMI have been the focus of research for several decades. Insights from these studies have led to several therapeutic interventions that improve outcome. In addition to depressed systo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
92
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(102 citation statements)
references
References 91 publications
(74 reference statements)
5
92
1
4
Order By: Relevance
“…Incorporation of trastuzumab enhances cardiotoxicity, with published incidences for heart failure ranging from 1.7% to 16% and for asymptomatic left ventricular dysfunction ranging from 6% to 34% [4][5][6][7]. Diastolic dysfunction is an important predictor of all-cause mortality in large epidemiologic studies [8] and has been shown to play an essential role in the pathophysiology of other cardiac diseases [9,10] (e.g., ischemic heart disease, hypertensive heart disease, or myocarditis), with pathology similar to anthracycline-related cardiotoxicity [11]. Diastolic dysfunction, in this instance, contributes to the onset of heart failure and has been shown to precede the development of systolic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of trastuzumab enhances cardiotoxicity, with published incidences for heart failure ranging from 1.7% to 16% and for asymptomatic left ventricular dysfunction ranging from 6% to 34% [4][5][6][7]. Diastolic dysfunction is an important predictor of all-cause mortality in large epidemiologic studies [8] and has been shown to play an essential role in the pathophysiology of other cardiac diseases [9,10] (e.g., ischemic heart disease, hypertensive heart disease, or myocarditis), with pathology similar to anthracycline-related cardiotoxicity [11]. Diastolic dysfunction, in this instance, contributes to the onset of heart failure and has been shown to precede the development of systolic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…3) [21,22]. Показано, что рестриктив-ный тип наполнения ЛЖ у пациентов с ОИМ явля-ется мощным независимым предиктором поздней дилатации ЛЖ и сердечно-сосудистой смертности [23]. В исследовании Nijland F, et al [24] укорочение времени замедления раннего наполнения (пик E) было описано как наилучший предиктор сердечно-сосудистой смертности у пациентов, госпитализиро-ванных по поводу ОИМ.…”
Section: прогностическая значимость эхокардиографии после острого инфunclassified
“…(2) In recent studies, both left ventricle (LV) systolic and diastolic function assessed by echocardiography have been shown to predict cardiovascular events in ACS patients .However, little is known about left atrium (LA) function which is an integral part of overall cardiac function in predicting the prognosis of ACS patients. (3)(4)(5)(6) Echocardiography is now the most commonly used noninvasive tool for the assessment of cardiac anatomy and function. In addition to commonly established roles such as confirming diagnosis, etiologic work-up, complication screening, and disease monitoring, echocardiography plays an important clinical role in prognostic assessment.…”
Section: Introductionmentioning
confidence: 99%